2018
DOI: 10.47762/2017.964x.19
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Aquacrop for Different Irrigation Regimes of Onion (<i>Allium Cepa</i>) in Bontanga Irrigation Scheme

Abstract: Crop water productivity models are important tools in evaluating the effect of different irrigation regime on crop yield. AquaCrop model is a crop water productivity model adopted by the Land and Water Division of FAO in the year 2009. It simulates yield response to water for herbaceous crops, and it is particularly suitable in addressing conditions where water is a key limiting factor in crop production such as in northern Ghana. The objective of this study was to calibrate the AquaCrop model for different ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…The result revealed that irrespective of the level of irrigation and mulch, the observed values for both Onion bulb yield and biomass recorded were underestimated by the Aqua-Crop model except at 100% irrigation with white synthetic mulch with a % deviation of 0.7. The result was in line with a report by Agbemabiese et al (2017) which suggested that crop yields were overestimated at 10% irrigation level and underestimated at deficit levels. The highest model values of 6.09 ton ha-and 8.24 ton ha-1 of bulb yield and biomass respectively were recorded at 100% irrigation under white synthetic mulch.…”
Section: Model Calibration and Validationsupporting
confidence: 92%
See 1 more Smart Citation
“…The result revealed that irrespective of the level of irrigation and mulch, the observed values for both Onion bulb yield and biomass recorded were underestimated by the Aqua-Crop model except at 100% irrigation with white synthetic mulch with a % deviation of 0.7. The result was in line with a report by Agbemabiese et al (2017) which suggested that crop yields were overestimated at 10% irrigation level and underestimated at deficit levels. The highest model values of 6.09 ton ha-and 8.24 ton ha-1 of bulb yield and biomass respectively were recorded at 100% irrigation under white synthetic mulch.…”
Section: Model Calibration and Validationsupporting
confidence: 92%
“…This could be as a result of a larger % deviation of ETa that was observed at water-stressed plots. This result was in line with the findings byAgbemabiese et al (2017) which states that the Aqua-Crop model underestimated ETwp. The % deviation observed between the observed and simulated ETwp values were fairly estimated for most of the treatments as shown in Table4.…”
supporting
confidence: 92%